Who is the Indian Farmer? - Bedide (Kuffir), Naren (Prabuddha: Journal of Social Equality, 2019)
In this interview, the fundamental question of ‘who is a farmer’ is examined in the context of purported capitalist expansion in India. It attempts to define the average Indian farmer in terms of labor, ambiguous property rights and exploitation and examines caste mode of production.